HAPPY PILLS: A GENEALOGY OF CONTEMPORARY PSYCHOPHARMACEUTICALS - de Azevedo Soares, Silvio [UNESP] (Universidade Federal do Para, 2024)
In this text, I discuss how psychopharmaceuticals reached the status of the main micropolitical technology of current psychiatry. For this, I analyze the following processes: a) the specification and industrial production of these drugs; b) the consolidation of neurobiological psychiatry with the third edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM III); c) the emergence of a new generation of psychotropic drugs: selective serotonin reuptake inhibitors (SSRIs). Throughout the text, I bring contributions to the arguments of Nikolas Rose (molecular biopolitics) and Paul Preciado (pharmacopower).
PÍLULAS DA FELICIDADE: UMA GENEALOGIA DOS PSICOFÁRMACOS CONTEMPORÂNEOS
Keywords: biopolitics; genealogy; pharmacopower; psychiatry; psychopharmaceuticals